2022
DOI: 10.1558/jasr.22810
|View full text |Cite
|
Sign up to set email alerts
|

Selling (Con)spirituality and COVID-19 in Australia

Abstract: Conspirituality—the merger of conspiracy theories and spirituality—has attracted significant global media and scholarly attention during the COVID-19 pandemic. This article expands upon the ‘two core’ conspiritual convictions proposed by Ward and Voas that ‘1) a secret group covertly controls, or is trying to control, the political and social order, and 2) humanity is undergoing a “paradigm shift” in consciousness’. We identify an additional ten key convictions central to (con)spirituality, including those tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Their research also revealed a good deal of (6) white privilege in the movement, “with their emphasis on strong and healthy white bodies and immune systems, and belief in abundance,” (p. 153)—this privilege allows adherents to conspirituality to use their “spiritual narratives” to “avoid difficult issues, in this case, the reality and severity of the pandemic” (p. 153). Halafoff and others (2022) also found a strong sense of and desire for (7) authenticity, autonomy, and individual expressivity in the movement, along with (8) a desire to join “spiritual tribes” full of like‐minded “seekers.” In addition, conspiritualists (9) are characterized by vaccine hesitancy and/or refusal, (10) spread their message through evangelizing, (11) monetize their beliefs through selling conspirituality, and (12) embrace a kind of “sciencey‐spirituality,” where the movement and individuals within it draw on “scientific research and pseudo‐scientific ‘evidence’ to bolster their claims of efficacy” (p. 157) while also dismissing the work of actual scientists. And in a study of prominent conspirituality influencers Pete Evans, David Avocado Wolfe, Kelly Brogan, and Sacha Stone, Baker (2022) sought to understand the “key techniques these influencers use to establish and sustain visibility and status online” (p. 7).…”
Section: From Pastel Q To Conspiritualitymentioning
confidence: 98%
See 1 more Smart Citation
“…Their research also revealed a good deal of (6) white privilege in the movement, “with their emphasis on strong and healthy white bodies and immune systems, and belief in abundance,” (p. 153)—this privilege allows adherents to conspirituality to use their “spiritual narratives” to “avoid difficult issues, in this case, the reality and severity of the pandemic” (p. 153). Halafoff and others (2022) also found a strong sense of and desire for (7) authenticity, autonomy, and individual expressivity in the movement, along with (8) a desire to join “spiritual tribes” full of like‐minded “seekers.” In addition, conspiritualists (9) are characterized by vaccine hesitancy and/or refusal, (10) spread their message through evangelizing, (11) monetize their beliefs through selling conspirituality, and (12) embrace a kind of “sciencey‐spirituality,” where the movement and individuals within it draw on “scientific research and pseudo‐scientific ‘evidence’ to bolster their claims of efficacy” (p. 157) while also dismissing the work of actual scientists. And in a study of prominent conspirituality influencers Pete Evans, David Avocado Wolfe, Kelly Brogan, and Sacha Stone, Baker (2022) sought to understand the “key techniques these influencers use to establish and sustain visibility and status online” (p. 7).…”
Section: From Pastel Q To Conspiritualitymentioning
confidence: 98%
“…Australian sociologists Halafoff and others (2022), in their study of published literature, opinion pieces, and podcasts, found 10 additional conspiritual convictions held by conspiritualists or common in the movement. In addition to (1) a belief that we are in the middle of a paradigm shift and (2) that a New World Order is trying to control the political and social order (outlined already by Ward and Voas, 2011), they found (3) a belief that conspiritualists are in a “Cosmic War” and that they are spiritual warriors fighting on the side of good versus evil, (4) an opposition to mainstream culture, and (5) a belief in the exceptionalism and exclusivity of their New Age perspective—it is not available to all, only those who are enlightened.…”
Section: From Pastel Q To Conspiritualitymentioning
confidence: 99%
“…Vaccine hesitancy is closely linked to conspiracy beliefs and esotericism: Several conspiracy theories target vaccinations directly (e.g., by claiming that the vaccines implant microchips that serve to control humans), and conspiracy beliefs appear to be the strongest psychological predictor of antivaccination attitudes (Hornsey et al, 2018). Members of esoteric communities often adhere to a pseudoscientific lay theory of immunity , which views a natural diet and lifestyle as sufficient to ensure immunity, and vaccines as a harmful disruption of the workings of the immune system (Halafoff et al, 2022). Thus, it seems unsurprising that alternative spirituality consistently predicts vaccine hesitancy across multiple countries (Rutjens et al, 2022; Rutjens & van der Lee, 2020).…”
Section: Conspiracy Beliefs and Coronavirus Downplayingmentioning
confidence: 99%
“…This in itself is not problematic, as many argue for the need to draw on First Nations, Asian, and pre-modern/ non-materialist frameworks of interdependence to counter anthropocentrism and for world-repairing (Halafoff, 2021;Yunkaporta, 2019Yunkaporta, , 2022. While many people turned to various spiritual practices as supports during the COVID-19 crisis (Halafoff et al, 2020a(Halafoff et al, , 2021, the CSCA study also revealed a more disturbing spiritual exceptionalism, in which some wellness influencers positioned themselves as having access to the 'real' and 'hidden' truth behind the pandemic and sought to convince others that they were in a spiritual war, and of the need to resist lockdowns and vaccine mandates that were threatening their freedom and sovereignty (Halafoff et al, 2020c(Halafoff et al, , 2021(Halafoff et al, , 2022b.…”
Section: (Con)spirituality Science and Covid-19 In Australiamentioning
confidence: 99%
“…Scholars have long examined religion’s and spirituality’s relationship to capitalism, and in more recent years how the burgeoning ‘spiritual marketplace’ (Roof, 1999) can still facilitate a sincere engagement with spirituality for personal, social, and planetary wellbeing (Jain, 2014, 2020; Gauthier, 2020). Further ambivalence has also been revealed in recent studies regarding neoliberal spirituality’s capacity to be both peacebuilding and violent (Appleby, 1999; Halafoff et al, 2022b).…”
Section: The Spiritual Revolution?mentioning
confidence: 99%